Mathematical model of dynamic interaction between wheel-set and rail track - Bureika, Gintautas; Subačius, Rimantas (Transport, 2002)
The main goal of this title is to show how the effects on maximum bending tensions at different locations in the track caused by simultaneous changes of the various parameters can be estimated in a rational manner The dynamic of vertical interaction between a moving rigid wheel and a flexible railway track is investigated. A round and smooth wheel tread and an initially straight and non-corrugated rail surface are assumed in the present optimisation study. Asymmetric linear three-dimensional beam structure model of a finite length of the track is suggested including rail, pads. sleepers and ballast with spatially non-proportional damping. Transient bending tensions in sleepers and rail are calculated. The influence of eight selected track parameters on the dynamic behaviour of the track is investigated. A two-level fractional factmial design method is used in the search for a combination of numerical levels of these parameters making the maximum bending tensions the minimum. Finally, the main conclusions are given. First Published Online: 19 Oct 2011